Dual Careers of Athletes During COVID-19 Lockdown - Izzicupo, Pascal; Di Baldassarre, Angela; Abelkalns, Ilvis; Bisenieks, Ugis; Sánchez-Pato, Antonio; Cánovas-Alvarez, Francisco José; Doupona, Mojca; Figueiredo, António J.; García-Roca, Juan Alfonso; Ghinassi, Barbara; Leiva-Arcas, Alejandro; Meroño, Lourdes; et al. (Frontiers in Psychology, 2021)
This study aimed to investigate the student-athletes’ capability to face the academic, sport, and social challenges during the COVID-19 lockdown, and to disclose novel aspects of dual career. A 32-item online survey encompassing demographic characteristics, sport and university engagement, support and dual-career benefits, physical activity, sitting time, and the time deemed necessary to recover the previous level of performance was developed. Four hundred sixty-seven student-athletes (males: 57%, females: 43%), from 11 countries, competing in 49 different sports (individual: 63.4%, team: 36.6%) at regional (17.5%), national (43.3%), and international (39.2%) levels, and enrolled at high school (21.9%) and university (78.1%) levels completed the survey. During the lockdown, the respondents decreased the time dedicated to sport and academics, although they maintained an active lifestyle. Student-athletes from countries under severe contagion were more likely to train at home, dedicate to academics, and receiving support from the coach, but less likely receiving support from their teachers. With respect to their team sport counterparts, athletes competing in individual sports trained more and were more likely to receive support from their coaches. International athletes showed the highest training time and support from their coaches and as student-athletes. High-school students received more support from their coaches and teachers, whereas university students were more likely considering dual career useful to cope with the COVID-19 pandemic. This study substantiates the relevant role of competitive sports participation in the maintenance of active lifestyles, with student-athletes considering home training and e-learning valuable resources during the lockdown. Furthermore, their sport and academic commitments helped student-athletes coping with the emergency of the COVID-19 pandemic.